Entomological aspects of Chagas disease in Huallaga and Picota, San Martin, Peru - Cáceres, Abraham G. (2010)
ntroduction: There is little and not recent information on the presence of triatomine bugs in San Martin department, Amazon area of our country where Chagas disease has been reported by wild triatomine insects as vectors. Objectives: To determine the geographic distribution of hematophagous triatomine insects in Huallaga and Picota provinces, San Martin department, Peru. To determine the domiciliary infestation by triatomine vectors indexes, trypano-triatomine infection as well as their dispersion. To determine the insects feeding source and to genetically characterize the tripanosomatidae they carry. Design: Observational and descriptive study. Setting: Health and Laboratories region networks. National Institute of Health laboratories. Participants: Houses from 6 districts of Huallaga province and 9 from Picota province (San Martin department). Interventions: Triatomine insect’s collection was carried out in 3 362 homes located in semi-urban and rural zones accounting for 30% of the total area of studied provinces. Feeding preferences were assessed by a precipitin test using specific antibodies against guinea pig, dog, cat, chicken and human beings sera. Trypanosomes were isolated by inoculation of stool samples from infected insects in Balb/c mice and using axenic culture media. Genetic characterization was done by PCR amplification of the genome by gene intergenic spacer of the miniexon. Main outcome measures: To assess if Huallaga and Picota, San Martin, Peru, are Chagas disease risk areas. Results: In 46 of the 3 368 homes visited, 53 triatomine adults were collected belonging to the species Rhodnius pictipes (56,6%), Panstrongylus geniculatus (41,5%) and Eratyrus mucronatus (1,9%). For the first time, P. geniculatus was reported in both provinces included in the study. Domiciliary infestation index was 1,4%, trypano-triatomine infection index was 3,8% and dispersion index was 30,1%. For R. pictipes 5 sources of food were identified (chicken, human, dog, guinea pig and cat) and for P. geniculatus, a mix feed: dog, cat and chicken. Trypanosoma spp. isolates of R. pictipes from Sacanche (Huallaga) belonged to T. cruzi TCI (350 pb); similar result was obtained in 10 clones studied. Conclusions: Results indicate that R. pictipes and P. geniculatus are undergoing colonization of the regions included in this study. Within the province of Huallaga, R. pictipes is the predominant vector of T. cruzi; therefore these locations must be considered high risk areas for Chagas disease.